Da eficácia dos direitos fundamentais no trabalho: uma análise crítico-comparativa - Abreu, Fernanda de Miranda Santos Cezar de (2018)
The research undertaken aims to analyze the effectiveness of this select list of rights in the international sphere. We sought to establish what would be the requirements for a legal system to be considered effective, that is, the basic premises for establishing whether a given legal framework could be considered effective or not. The concepts outlined here are the first steps for the analysis that we undertake in the following chapters. The normative production of the International Labor Organization will also be analyzed, as well as the construction and consolidation of the Fundamental Rights at Work, culminating in the 1998 Declaration. Fundamental Rights at Work are restricted to the International Labor Organization, initiatives and acts in other international spheres. In the third chapter, we will consider how these rights are treated in different international spheres: the Bretton Woods System, the United Nations, the Organization for Economic Co-operation and Development, the European Union, Mercosur, and finally the Private Codes of Conduct. An important issue to be considered is the non-observance of Convention 29 of the ILO (Forced Labor Convention, 1930) by Myanmar and the consequences of such disrespect. After historically contextualizing the case, will be analyze the treatment given to the case by the ILO and other international entities, including by sovereign states. Because it is a descriptive and exploratory study, it will be carried out based on bibliographical and historical research, sometimes using the deductive method and others the inductive, mainly in the criticisms and reflections about the normative texts